THE HIGHER ORDER MODES IN THE OPEN RESONATOR WITH THE SEGMENT OF THE CIRCULAR WAVEGUIDE - Ilchenko, M. E.; Kuzmichev, I. K.; Narytnik, T. N.; Denbnovetsky, S. V.; May, A. V. (Видавничий дім «Академперіодика», 2019)
PACS number: 07.57.-cPurpose: Study of the TE01 wave excitation efficiency in a segment of the circular waveguide located in the center of one of the mirrors of the open resonator with the help of the higher order mode TEM30q (in the Hermite-Gauss functions) and the degenerate mode TEM*11q.Design/methodology/approach: To determine the TE01 wave excitation efficiency in a segment of a circular waveguide using the higher resonator oscillations, an aperture area ratio of the mirror antennas is used. Loaded Q-factors of a hemispherical open resonator and a resonator with a circular waveguide segment are determined by the width of the resonance curve at the level of –3 dB.Findings: It has been established that the  TE01  wave maximum excitation efficiency in a circular waveguide when using the TEM30q mode is 0.121 with the circular waveguide radius relative value being 0.993, and using the TEM*11q mode it is 0.242 for the same radius value. When the considered wave was excited by using only the central part of the TEM*11q, which field amplitude distribution on the open resonator mirror corresponds to the two rings, then the TE01 wave maximum excitation efficiency grew up to 0.954. Experimental studies were made in the two-millimeter wavelength range. The results of the made measurements showed that due to the circular waveguide segment the  TEM30q mode transformed into the TEM*11q mode which stably exists in the resonator during its tuning. In this case, the presence of a circular waveguide segment does no result in the decrease of the loaded Q-factor of the resonance system.Conclusions: The here proposed quasi-optical resonant system can be used as a highly efficient power combiner in the subterahertz frequency range.Key words: open resonator, circular waveguide, excitation efficiency, power combinerManuscript submitted 10.07.2019Radio phys. radio astron. 2019, 24(3): 218-226REFERENCES1. AGRANAT, M. B., IL’INA, I. V. and SITNIKOV, D. S., 2017. Application of terahertz spectroscopy for remote express analysis of gases. Teplofizika vysokikh temperatur. vol. 55, no. 6, pp. 759–774. (in Russian). DOI: https://doi.org/10.7868/S00403644170601142. HAFEZ, H. A., CHAI, X., IBRAHIM, A., MONDAL, S., FÉRACHOU, D., ROPAGNOL, X. and OZAKI, T., 2016. Intense terahertz radiation and their applications. J. Opt. vol. 18, no. 9, id. 093004. DOI: https://doi.org/10.1088/2040-8978/18/9/0930043. YANG, X., ZHAO, X., YANG, K., LIU, Y., FU, W. and LUO, Y., 2016. Biomedical Applications of Terahertz Spectroscopy and Imaging. Trends Biotechnol. vol. 34, no. 10, pp. 810–824. DOI: https://doi.org/10.1016/j.tibtech.2016.04.0084. LYUBCHENKO, V. E., YUNEVICH, E. O., KALININ, V. I., KOTOV, V. D., RADCHENKO, D. E. and TELEGIN, S. A., 2015. Active microstrip antennas and antenna arrays with field-effect transistors. Radioelectronics. vol. 7, no. 1, pp. 3–14. DOI: https://doi.org/10.17725/rensit.2015.07.0035. BAE J., ABURAKAWA, Y., KONDO, H., TANAKA, T. and MIZUNO, K., 1993. Millimeter and submillimeter wave quasi-optical oscillator with Gunn diodes. IEEE Trans. Microw. Theory Tech. vol. 41, no. 10, pp. 1851–1855. DOI: https://doi.org/10.1109/22.2479326. JUDASCHKE, R., HOFT, M. and SCHUNEMANN, K., 2005. Quasi-optical 150-GHz power combining oscillator. IEEE Microw. Wirel. Compon. Lett. vol. 15, no. 5, pp. 300–302. DOI: https://doi.org/10.1109/LMWC.2005.8476607. DVORNIKOV, A. A. and UTKIN, G. M., 1974. Summation of power from numerous oscillators. Radiotekhnika i elektronika. vol. 19, no. 3, pp. 550–559. (in Russian).8. TYAGI, R. K. and SINGH, D., 1996. Quasi-optical resonator for power combining at W-band. Int. J. Infrared Milli. Waves. vol. 17, is. 2, pp. 385–391. DOI: https://doi.org/10.1007/BF020881619. ARKHIPOV, A. V., BELOUS, O. I., BULGAKOV, B. M. and FISUN, A. I., 2002. Millimeter wave power combiner based on a half-open resonator. Int. J. Infrared Milli. Waves. vol. 23, is. 3, pp. 507–516. DOI: https://doi.org/10.1023/A:101505412426810. KOGELNIK, H., 1964. Coupling and convertion coefficients for optical modes. In: Quasi-Optics. Proceedings of the Symposium on Quasi-Optics. Brooklyn, NY: Polytechnic Press, pp. 333–347.11. KUZMICHEV, I. K., 2009. Quasi-Optical Resonance Systems with Internal Inhomogeneities. Telecommun. Radio Eng. vol. 68, no. 4, pp. 299–317. DOI: https://doi.org/10.1615/TelecomRadEng.v68.i4.3012. MENZEL, R., 2007. Photonics: Linear and Nonlinear Interactions of Laser Light and Matter. Berlin, Heidelberg, New York: Springer. ISBN 978-3-540-23160-8.13. KUZMICHEV, I. K., 2002. The probe diameter choosing for the investigation of the field distribution in the small aperture open resonator. Telecomm. Radio Eng. vol. 58, no. 7-8, pp.59–63. DOI: https://doi.org/10.1615/TelecomRadEng.v58.i7-8.50